Dietary patterns, metabolomic profile, and nutritype signatures associated with type 2 diabetes in women with postgestational diabetes mellitus: MyNutritype study protocol - Hasbullah, Farah Yasmin; Mohd Yusof, Barakatun Nisak; Abdul Ghani, Rohana; Mat Daud, Zulfitri ’Azuan; Appannah, Geeta; Abas, Faridah; Shafie, Nurul Husna; Mohamed Khir, Hannah Izzati; Murphy, Helen R. (MDPI, 2022)
Women with previous gestational diabetes mellitus (post-GDM) have an increased risk of cardiometabolic diseases including type 2 diabetes (T2D). Current diabetes screening is based on the oral glucose tolerance test without nutritional assessments, even though unhealthy dietary patterns were found to expedite disease progression in women post-GDM. While a healthful dietary pattern reduces T2D risk, limited data support a dietary pattern tailored to the Asian population, especially in the Malaysian context. Metabolomic profiles associated with dietary patterns in this population are also lacking. The proposed study aims to investigate both components of dietary patterns and metabolomic profile, known as nutritype signatures, and their association with T2D in women post-GDM. The comparative cross-sectional study will involve a minimum of 126 Malaysian women post-GDM aged 18–49 years. Dietary patterns will be analysed using principal component analysis. Plasma and urinary metabolites will be quantified using one-dimensional proton nuclear magnetic resonance (1H NMR) spectroscopy. The aim of the study is identifying the nutritype signatures associated with T2D. The findings will support the development of early prevention measures against T2D in women post-GDM.